2023
DOI: 10.1038/s41598-023-38357-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training and gut microbiome-associated metabolic shifts in women with overweight: a multi-omic study

Abstract: Physical activity is essential in weight management, improves overall health, and mitigates obesity-related risk markers. Besides inducing changes in systemic metabolism, habitual exercise may improve gut’s microbial diversity and increase the abundance of beneficial taxa in a correlated fashion. Since there is a lack of integrative omics studies on exercise and overweight populations, we studied the metabolomes and gut microbiota associated with programmed exercise in obese individuals. We measured the serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…We did not investigate the mechanism underlying the training-induced increase in aromatic lactic acids. However, increases in faecal concentrations have previously been reported for PLA [47], ILA and HPLA [48] in subjects with obesity participating in endurance exercise interventions. This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not investigate the mechanism underlying the training-induced increase in aromatic lactic acids. However, increases in faecal concentrations have previously been reported for PLA [47], ILA and HPLA [48] in subjects with obesity participating in endurance exercise interventions. This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…However, increases in faecal concentrations have previously been reported for PLA [47], ILA and HPLA [48] in subjects with obesity participating in endurance exercise interventions. This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50]. Interestingly, a recent study found that serum ILA and HPLA were increased in both lean and obese subjects following an exercise intervention, whereas faecal levels were increased in the obese cohort only [48].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies present the benefits of exercise on metabolic health via an increase of SCFA-producing bacteria ( 137 140 ). A study comparing the effect of exercise in lean and obese individuals, however, did not show a significant shift in microbial metabolism for the latter ( 139 ).…”
Section: Scfa Production In the Gutmentioning
confidence: 99%
“…The connection between the gut microbiome and exercise carries substantial implications for athletes, and potential mechanisms are discussed here (Wegierska et al 2022 ). Recent research conducted on overweight women unveiled the potential of aerobic exercise to induce metabolic shifts that provide substrates for beneficial gut microbiota, such as Akkermansia (Hintikka et al 2023 ). Additionally, a recent systematic review concluded that moderate-to high-intensity exercise (30–90 min) performed at least three times per week for more than 8 weeks can effectively alter the gut microbiota in both clinical and healthy individuals (Boytar et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%